2021
DOI: 10.1002/imed.1025
|View full text |Cite
|
Sign up to set email alerts
|

Whole tumor cell vaccines engineered to secrete GM‐CSF (GVAX)

Abstract: Generation of immunity against cancer through vaccination has long been an elusive goal for tumor immunologists. Putative candidates for vaccination targets include oncofetal antigens, viral antigens, neoantigens, and differentiation antigens. The first attempts at cancer vaccination used injections of whole autologous tumor cells. However, these unmodified tumor cells did not engender a robust immune response. Subsequent efforts were focused at enhancing the immunogenicity of whole autologous tumor cell vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 94 publications
0
8
0
Order By: Relevance
“…Nevertheless, several immortalized cell lines have been clinically tested in immuno-oncology, including the K562 line, a human erythroleukemic cell line that served as the backbone of multiple clinical trials over the last decades without safety concerns. 69 , 70 In addition, the reported cell line is intended to be solely used with macroencapsulation technology, which is a semipermeable macrocapsule. The cells never come into contact with the patient, and the implant can be extracted from the body at all time.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, several immortalized cell lines have been clinically tested in immuno-oncology, including the K562 line, a human erythroleukemic cell line that served as the backbone of multiple clinical trials over the last decades without safety concerns. 69 , 70 In addition, the reported cell line is intended to be solely used with macroencapsulation technology, which is a semipermeable macrocapsule. The cells never come into contact with the patient, and the implant can be extracted from the body at all time.…”
Section: Discussionmentioning
confidence: 99%
“…The dramatic success of immune checkpoint blockade immunotherapy has revived interest in cancer vaccines, which might provide a complementary means to help eliminate primary and distant tumors and then maintain durable surveillance against recurrence. 28 29 Most recent efforts to increase immunogenicity of lethally irradiated tumor cell vaccines have relied on engineering the cells to express GM-CSF or other cytokines toward promoting antigen uptake and presentation, with several examples under clinical investigation such as GVAX for pancreatic and prostate cancers 30 and Vigil for ovarian cancer. 31 Among many alternative strategies to produce immunogenic whole tumor cell vaccines, preclinical studies have reported encouraging results with early ferroptotic cells, 32 necroptotic cells 33 and etoposide-injured cells.…”
Section: Discussionmentioning
confidence: 99%
“…Whole tumor cell vaccines have attracted attention because they contain the complete antigen spectrum of tumor cells [ 27 , 69 ]. The first attempt at a cancer vaccine in the early 20th century involved the injection of whole autologous tumor cells [ 70 ]. A complete set of autologous antigens includes epitopes recognized by CD8 + CTLs and by CD4 + helper T cells, inducing powerful T cell activation [ 71 ].…”
Section: Tumor Cell-derived Vaccinesmentioning
confidence: 99%
“…GVAX Pancreas combined with CRS-207 prolonged the survival of patients with metastatic pancreatic cancer in clinical trials [ 79 ]. GVAX has also been combined with other treatments, but the clinical efficacy did not meet expectations [ 70 , 76 , 80 ]. As tumor stromal cells also contribute to the progression and metastasis of tumors, they should be eliminated to achieve better therapeutic efficacy against tumors [ 81 ].…”
Section: Tumor Cell-derived Vaccinesmentioning
confidence: 99%